Validity and Reliability of Instruments for Measuring Phubbing Behavior in High School and Equivalent Students - Pratiwi, Awalya Siska; Setiyowati, Arbin Janu; Khalid, Fariza (Buletin Konseling Inovatif, 2025)
These four causes of phubbing—smartphone addiction, internet addiction, social media addiction, and gaming addiction—are interconnected. The purpose of this article is to develop an instrument that counselors can use to determine the level of phubbing behavior among students in their school by testing its validity and reliability. The steps taken include: (1) determining aspects of the phubbing behavior scale, (2) formulating phubbing behavior scale indicators, (3) formulating phubbing behavior scale descriptors, (4) compiling phubbing behavior scale statement items, (5) testing validity, and (6) testing the reliability of the instrument. The 143 respondents consisted of students from several schools, including Maharani Pharmacy Vocational School Malang, National Vocational School Malang, State Senior High School 1 Gambiran, Widyagama High School Malang, Dr. Soetomo High School, and Vocational High School Darissulaimaniyyah. All respondent schools were located in East Java, Indonesia. After obtaining data from the students, it was analyzed using IBM SPSS Statistics 26 to test the validity and reliability of the phubbing behavior scale. The phubbing behavior scale indicators were derived from aspects such as communication disorders and obsession with cell phones. The scale, initially composed of 23 statement items, was found to have one invalid item, number 13, after testing. Thus, the remaining valid items totaled 22.